Saint Trophymus of Arles, the patron of sufferers from podagra - P. Marson (PAGEPress Publications, 2001)
Among the large number of saints patronizing the sufferers from gout, St. Trophymus of Arles, that lived in the first times of Christianity, is a very interesting figure, by enjoying a particular devotion in Rome during the XVII/XVIII centuries. Such a veneration, as widely described by Anton Maria Bonucci in the agiographic essay "Istoria di S. Trofimo, Arcivescovo di Arles, Primate in Francia, e Avvocato de' Podagrosi" (1711), was promoted by the Roman Congregation of the Five Wounds of Jesus Christ and practised at the San Filippo Neri's Church in via Giulia. In the present study, besides some biographical notes, it has been told how the cult of gouty subjects to St. Trophymus has been founded in Rome and displayed in a solemn fashion.